Self-sensing and self-heating basalt fiber composite material and preparation method thereof
By embedding the prepared conductive composite film on the surface of the basalt fiber composite material, self-perception and self-heating functions are achieved, solving the problem of existing materials lacking real-time health monitoring and extreme environmental adaptation, and improving the safety and reliability of the materials.
Patent Information
- Application Number
- CN202510388901.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing basalt fiber composites lack self-perception and self-heating functions, and cannot monitor the healthy state of the structure in real time and prevent freezing and cracking in extreme environments, affecting its safety and reliability.
By adding a layer of polypropylene film to the two layers of carbon nanotube conductive films, the conductive composite film is prepared by hot pressing and embedded into the surface of the basalt fiber composite material to achieve self-perception and self-heating functions.
This method improves the mechanical properties and production efficiency of basalt fiber composite materials, realizes the sensitivity of self-perception functions and the rapid response of self-heating functions, and ensures the stable performance of the material in extreme environments.
Smart Images

Figure CN119898084A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a self-sensing and self-heating basalt fiber composite material and a preparation method thereof, belonging to the technical field of fiber-reinforced composite materials. Background Art
[0002] With the continuous development of modern engineering technology, fiber-reinforced composite materials are widely used in aerospace, automobile manufacturing, building structures and other fields due to their excellent mechanical properties, corrosion resistance and lightweight characteristics. Among them, basalt fiber, as a new type of natural fiber, has gradually become an ideal material to replace traditional glass fiber and carbon fiber because of its advantages such as high strength, high modulus, high temperature resistance, corrosion resistance and environmental protection. In practical applications, basalt fiber composite materials not only have excellent mechanical properties, but also can withstand high temperatures and harsh environments. Therefore, they have broad application prospects in the fields of construction, transportation, energy, etc. However, in the current application of most basalt fiber composite materials, there is a lack of effective damage monitoring technology, and it is impossible to obtain damage information of the composite materials in a timely manner, and it is impossible to actively adjust the temperature of the material, which leads to structural failure when it is used for a long time in harsh environments, thereby affecting the safety and reliability of the structure.
[0003] Traditional fiber-reinforced composite materials cannot actively control their own temperature, especially in cold environments, and face the risk of freezing and cracking. The self-heating function enables fiber-reinforced composite materials to generate heat when necessary to prevent freezing, thereby ensuring the stability of the performance of fiber-reinforced composite materials under extreme conditions. The self-sensing function can monitor the structural health of the composite material in real time and detect cracks, deformation or other damage to the composite material in a timely manner, which is of great significance for improving structural safety and extending the service life of the material.
[0004] At present, there are three main technologies for giving fiber-reinforced composite materials the functions of self-sensing and self-heating, namely, depositing conductive particles on the fiber surface, adding conductive particles to the matrix, and embedding conductive films in the composite materials. Since the mechanical properties of fiber-reinforced composite materials are mainly borne by the fiber, depositing conductive particles on the fiber surface changes the fiber surface structure and affects the mechanical properties of the fiber. Moreover, it requires a relatively complex process to deposit conductive particles evenly on the fiber, which increases the production cost and process difficulty. In long-term use, the conductive particles are not tightly combined with the fiber surface, and the detachment will cause the performance of the fiber-reinforced composite material to decrease. When adding conductive particles to the matrix, the distribution of conductive particles is subject to the mixing properties and particle size of the material. Especially in high strain or fatigue environments, conductive particles are prone to aggregation, thereby affecting the accuracy of self-sensing. In addition, the addition of conductive particles will cause the viscosity of the matrix to increase sharply, which is not conducive to the composite material molding process. Compared with the other two methods, embedding conductive films in composite materials is easier to operate and evenly distributed in the composite material, which can achieve large-scale production. The conductive film has high conductivity and can achieve rapid heating. Its porous structure also facilitates the penetration of resin and achieves a firm bond with the composite material.
[0005] However, due to the poor mechanical properties of the conductive film, it is easy to be damaged during the preparation process. Therefore, we proposed to prepare a conductive composite film by adding a layer of polypropylene film to two layers of carbon nanotube conductive film, and embed it into the surface of basalt fiber composite material to realize self-sensing and self-heating functions. Compared with other self-sensing and self-heating fiber composite materials, the method proposed by the present invention has the characteristics of simple operation, high economic benefit, high sensitivity, and rapid heating. Summary of the invention
[0006] The present invention mainly overcomes the deficiencies in the prior art and proposes a self-sensing and self-heating basalt fiber composite material and a preparation method. The basalt fiber composite material prepared by the method gives the basalt fiber composite material electrical conductivity, so that the basalt fiber composite material has the functions of self-sensing and self-heating.
[0007] The technical solution provided by the present invention to solve the above technical problems is: a self-sensing and self-heating basalt fiber composite material and a preparation method thereof, comprising the following steps: S1. Dispersing carbon nanotubes and surfactants uniformly in deionized water by ultrasound, filtering and drying the obtained carbon nanotube solution to obtain a carbon nanotube conductive film; S2, hot pressing the polypropylene powder to obtain a polypropylene film; S3, sandwiching the polypropylene film obtained in S2 between two layers of carbon nanotube conductive films obtained in S1 and hot pressing to obtain a conductive composite film; S4, laminating the conductive composite film obtained in S3 and the basalt fiber fabric prepreg, and hot pressing to obtain a basalt fiber composite material; S5. Cut the basalt fiber composite material obtained in S4 into standard samples and connect electrodes using conductive silver glue.
[0008] A further technical solution is that the surfactant in step S1 is any two of polyvinyl pyrrolidone, sodium lauryl sulfate, and Triton X-100 and they are mixed in a ratio of 1:1.
[0009] A further technical solution is that the mass ratio of the carbon nanotubes to the surfactant in step S1 is 1:4, and the concentration of the carbon nanotubes is 0.5 mg / mL.
[0010] A further technical solution is that the filter membrane used for filtration in step S1 is a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm, and the filtration time is 90 minutes.
[0011] A further technical solution is that the thickness of the carbon nanotube conductive film in step S1 is 120-140 μm.
[0012] A further technical solution is that the hot pressing temperature in step S2 is 180°C, the pressure is 10 MPa, and the time is 30 min.
[0013] A further technical solution is that the thickness of the polypropylene film in step S2 is 120-150 μm.
[0014] A further technical solution is that the hot pressing temperature in step S3 is 180°C, the pressure is 1 MPa, and the time is 30-60 min.
[0015] A further technical solution is that in step S3, the thickness of the conductive composite film is 290-350 μm, wherein the thickness of the polypropylene film is 50-70 μm, and the thickness of the carbon nanotube conductive film is 120-140 μm.
[0016] A further technical solution is that in step S4, the number of basalt fiber fabric prepregs is 8 pieces, and the laying method of every 4 pieces is (0 / 90) / (±45) / (±45) / (0 / 90).
[0017] A further technical solution is that the lamination method in step S4 is to embed a piece of conductive composite film into the surface of the basalt fiber fabric prepreg.
[0018] A further technical solution is that the electrode installation position in step S5 is 5-7 mm away from both ends of the basalt fiber composite material.
[0019] A further technical solution is that in step S5, the electrode is installed in such a way that the electrode is in close contact with the sample and is wrapped around the sample in a width direction.
[0020] A further technical solution is that the conductive silver glue connects the electrode and the standard sample and has a thickness of 100-150 μm.
[0021] The second technical problem to be solved by the present invention is to provide a self-sensing and self-heating basalt fiber composite material prepared by the above method.
[0022] The present invention has the following beneficial effects: (1) The present invention prepares a conductive composite film by adding a layer of polypropylene film to two layers of carbon nanotube conductive films and hot pressing. Compared with the carbon nanotube conductive film, the mechanical properties of the conductive composite film are improved, thereby ensuring the integrity of the conductive composite film in the subsequent preparation process.
[0023] (2) A basalt fiber composite material is prepared by integrating a conductive composite film on the surface of a basalt fiber fabric prepreg. The porous structure of the conductive composite film is conducive to resin infiltration, thereby achieving a firm bond between the conductive composite film and the basalt fiber composite material, thereby ensuring the integrity of the conductive composite film and the basalt fiber composite material.
[0024] (3) A conductive composite film was prepared by a simple filtration and hot pressing method. The conductive composite film was further integrated on the surface of basalt fiber fabric prepreg to prepare basalt fiber composite materials. This method is simple to operate and can improve the production efficiency of basalt fiber composite materials and realize the large-scale production of basalt fiber composite materials.
[0025] (4) The present invention integrates a conductive composite film on the surface of the basalt fiber fabric prepreg to form a conductive network on the surface of the insulating basalt fiber composite material. When the composite material surface is subjected to external force or damaged, the original conductive path of the conductive composite film is deformed, resulting in a change in the resistance of the basalt fiber composite material. The damage of the basalt fiber composite material can be judged by the change in the resistance of the basalt fiber composite material. Since the conductive composite film has a dense conductive network, it has a high conductivity. When a voltage is applied to the basalt fiber composite material, due to the Joule effect, the surface of the basalt fiber composite material will heat up and the surface temperature will change with the voltage. Therefore, the conductive network on the surface of the basalt fiber composite material gives the basalt fiber composite material self-sensing and self-heating functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a preparation flow chart of the present invention; Figure 2are scanning electron microscope images of the cross section of the conductive composite film, wherein (a) is a scanning electron microscope image of the entire cross section of the conductive composite film, and (b) is a magnified scanning electron microscope image of a part of the cross section of the conductive composite film; Figure 3 Figures are mechanical properties of carbon nanotube conductive films and conductive composite films, where (a) is a stress-strain curve of the carbon nanotube conductive film and the conductive composite film, and (b) is a comparative bar graph of stress, strain and modulus of the carbon nanotube conductive film and the conductive composite film; Figure 4 The damage perception test diagram of basalt fiber composite materials, wherein (a) is an enlarged diagram of the damage perception test of basalt fiber composite materials when the strain is 0%-1.5%, and (b) is a damage perception test diagram of basalt fiber composite materials when the strain is 0%-4%; Figure 5 Figure 1 is a graph of the heating test of basalt fiber composite materials, where (a) is the change of the surface temperature of the basalt fiber composite material with time under different voltages, (b) is the change of the surface temperature of the basalt fiber composite material with increasing and decreasing input voltage, and (c) is the surface temperature of the basalt fiber composite material-U 2 Scatter plot, (d) is the long-term time-surface temperature curve of basalt fiber composite material under a constant voltage of 11V; Figure 6 This is an infrared thermal image of basalt fiber composite material. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the embodiments and drawings.
[0028] Example 1
[0029] like Figure 1 As shown, a self-sensing and self-heating basalt fiber composite material and a preparation method of the present invention are prepared by the following steps: Step 1: Use ultrasound to evenly disperse carbon nanotubes and surfactants in deionized water at a mass ratio of 1:4. Filter the obtained carbon nanotube solution with a concentration of 0.5 mg / mL through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm for 90 minutes and then dry to obtain a carbon nanotube conductive film with a thickness of 135 μm.
[0030] Step 2: The polypropylene powder was hot-pressed at a temperature of 180°C and a pressure of 10 MPa for 30 min to obtain a polypropylene film with a thickness of 120 μm.
[0031] Step 3: Sandwich the obtained polypropylene film between two layers of carbon nanotube conductive film, and hot press at a temperature of 180°C and a pressure of 1 MPa for 30 minutes to obtain a conductive composite film with a thickness of 320 μm, wherein the thickness of the polypropylene film is 50 μm and the thickness of the carbon nanotube conductive film is 135 μm.
[0032] Step 4: Lay the obtained conductive composite film and basalt fiber fabric prepreg, and hot-press to obtain a basalt fiber composite material.
[0033] The number of basalt fiber fabric prepregs is 8 pieces, and the laying method of every 4 pieces is (0 / 90) / (±45) / (±45) / (0 / 90), and a piece of conductive composite film is embedded on the surface of the basalt fiber fabric prepreg.
[0034] Step 5: Cut the obtained basalt fiber composite material into standard samples and use conductive silver glue to connect the electrodes to the standard samples.
[0035] The electrode installation position is 5 mm away from both ends of the basalt fiber composite material; the installation method is that the electrode is close to the sample and wrapped around the sample along the width direction; the conductive silver glue connects the electrode and the standard sample, and the thickness is 100 μm.
[0036] The conductive composite film prepared in step 1, step 2 and step 3 of Example 1 was observed for microscopic morphology, and its structure is as follows: Figure 2 shown.
[0037] Figure 2 It was revealed that the conductive composite film showed a multi-layer structure, with a polypropylene film in the middle and carbon nanotube conductive films on the upper and lower surfaces.
[0038] The carbon nanotube conductive film and the conductive composite film prepared in Example 1 were subjected to tensile test. The results are as follows: Figure 3 shown.
[0039] Figure 3 It was revealed that the addition of polypropylene film made the tensile strength of the conductive composite film higher than that of the carbon nanotube conductive film, and the addition of polypropylene film significantly improved the tensile properties of the carbon nanotube conductive film.
[0040] The basalt fiber composite material prepared in Example 1 was subjected to a three-point bending test, and the results are as follows: Figure 4 shown.
[0041] Figure 4The self-sensing function of basalt fiber composite materials with conductive composite films embedded on the surface was revealed. According to the stress-strain curve, the whole process can be divided into three stages, namely the elastic stage (0-0.9%), the damage initiation and growth stage (0.9-3.2%), and the fracture stage (3.2%-3.3%). In these three stages, the relative resistance changes in each stage are different, and the slope of the relative resistance change curve increases with the increase of stress, that is, the sensitivity also increases with the increase of stress.
[0042] In the elastic stage with a strain of 0-0.9%, the basalt fiber composite material undergoes elastic deformation, and its conductive network also undergoes elastic deformation, resulting in a change in the relative resistance of the basalt fiber composite material. In this stage, the sensitivity of the basalt fiber composite material is GF1, which is 0.5; At the damage initiation and growth stage with a strain of 0.9-3.2%, as the stress increases, matrix microcracks and crack extension, fiber breakage, fiber-matrix interface debonding and other damages appear in the basalt fiber composite material. These damages destroy the surface conductive network of the basalt fiber composite material, further increasing the relative resistance change. In this stage, the sensitivity GF2 of the basalt fiber reinforced composite material is 150.45 and GF3 is 233.42; In the fracture stage with a strain of 3.2-3.3%, as the stress continues to increase, the material breaks, the conductive network of the basalt fiber composite material is completely destroyed, and the relative resistance change value increases to infinity.
[0043] Figure 5 The self-heating function of basalt fiber composites with conductive composite films embedded on the surface was revealed. According to the temperature rise curve, the surface temperature of basalt fiber composites increased with the increase of applied voltage. When the applied voltage was 3V, the surface temperature could reach 26.3°C. When the applied voltage was 11V, the surface temperature could reach 75°C, and this temperature could be reached within 50s. Figure 5 As shown in (c), the heating of the basalt fiber composite material with a conductive composite film embedded on the surface conforms to Joule's law. Figure 5 As shown in (d), when the basalt fiber composite material is powered for a long time, its surface temperature remains basically unchanged, and stable heating can be achieved. Therefore, the self-heating of the basalt fiber composite material can be achieved by applying voltage, and the surface temperature of the basalt fiber composite material can be adjusted by controlling the voltage.
[0044] Figure 6 It was revealed that basalt fiber composites with conductive composite films embedded on the surface can be used for deicing. By utilizing its self-heating function, ice can be melted within 10 minutes and water can be heated to 66°C in 15 minutes, proving the self-heating ability of basalt fiber composites after integrating conductive composite films on the surface.
[0045] These results demonstrate that the basalt fiber composite material prepared in Example 1 can self-sensing and self-heating.
[0046] The above description is not intended to impose any form of limitation on the present invention. Although the present invention has been disclosed through the above embodiments, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a self-sensing and self-heating basalt fiber composite material, characterized in that: The following steps are involved: S1. Dispersing carbon nanotubes and surfactants uniformly in deionized water by ultrasound, filtering and drying the obtained carbon nanotube solution to obtain a carbon nanotube conductive film; S2, hot pressing the polypropylene powder to obtain a polypropylene film; S3, sandwiching the polypropylene film obtained in S2 between two layers of carbon nanotube conductive films obtained in S1 and hot pressing to obtain a conductive composite film; S4, laminating the conductive composite film obtained in S3 and the basalt fiber fabric prepreg, and hot pressing to obtain a basalt fiber composite material; S5. Cut the basalt fiber composite material obtained in S4 into standard samples and connect the electrodes using conductive silver glue.
2. The method for preparing a self-sensing and self-heating basalt fiber composite material according to claim 1, characterized in that: The surfactant in step S1 is any two of polyvinyl pyrrolidone, sodium lauryl sulfate and Triton X-100, mixed in a ratio of 1:
1.
3. The method for preparing a self-sensing and self-heating basalt fiber composite material according to claim 1, characterized in that: The mass ratio of carbon nanotubes to surfactant in step S1 is 1:4; the concentration of carbon nanotubes is 0.5 mg / mL; the thickness of the carbon nanotube conductive film is 120-140 μm; the filter membrane used for filtration is a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm, and the filtration time is 90 min.
4. The method for preparing a self-sensing and self-heating basalt fiber composite material according to claim 1, characterized in that: The hot pressing temperature in step S2 is 180°C, the pressure is 10MPa, and the time is 30min; the thickness of the polypropylene film is 120-150μm.
5. The method for preparing a self-sensing and self-heating basalt fiber composite material according to claim 1, characterized in that: The hot pressing temperature in step S3 is 180°C, the pressure is 1MPa, and the time is 30-60min; the thickness of the conductive composite film is 290-350μm, of which the thickness of the polypropylene film is 50-70μm, and the thickness of the carbon nanotube conductive film is 120-140μm.
6. The method for preparing a self-sensing and self-heating basalt fiber composite material according to claim 1, characterized in that: The number of basalt fiber fabric prepregs in step S4 is 8 pieces, and the laying method of every 4 pieces is (0 / 90) / (±45) / (±45) / (0 / 90); the laying method in step S4 is to embed a piece of conductive composite film into the surface of the basalt fiber fabric prepreg.
7. The method for preparing a self-sensing and self-heating basalt fiber composite material according to claim 1, characterized in that: In step S5, the electrode is installed at a position 5-7 mm away from both ends of the basalt fiber composite material, and the electrode is installed in close contact with the sample and wrapped around the sample along the width direction; the conductive silver glue connects the electrode and the standard sample, and has a thickness of 100-150 μm.
8. A self-sensing and self-heating basalt fiber composite material, characterized by: The self-sensing and self-heating basalt fiber composite material is prepared according to the preparation method of any one of claims 1-7.
Citation Information
Patent Citations
Preparation method of epoxy resin based composite material with controllable toughness
CN105733193A
Multi-wall carbon nanotube film / glass fiber reinforced resin composite material, preparation method and application thereof
CN110126384A
Preparation method of portable electric heating element based on carbon nanotube film
CN111542140A
Non-autoclave electroforming composite material method based on carbon nanomaterial
CN113696513A
Preparation method of carbon fiber / graphene composite electromagnetic shielding prepreg
CN115464941A